A Revisit of Gricean Maxims in Manado Malay Language - Ngenget, Stevanus (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Some researchers have tried to challenge the dominance of Gricean maxims in terms of its consistency. One way of testing it is by conducting research in vernacular language. This research is therefore conducted to revisit Gricean maxims in Manado Malay language, a language used by the people who live in Manado and its surroundings. This research, therefore, aims to find out (1) how the Cooperative Principle is violated in Manado Malay language, and (2) what the purpose of the generated implicatures are. The data used for analysis in this research were taken from recorded lunch break conversation of the lecturers at Unika De La Salle Manado in July 2016. The result showed that the Gricean maxims: maxim of quantity, maxim of quality, maxim of relation and maxim of manner were observed in Manado Malay language. It was also found that implicatures generated in Manado Malay language were meant for giving information. It can be concluded that Gricean maxims are consistent when implicatures occur in Manado Malay language. Furthermore, speakers of Manado Malay language usually produce implicature to give information and to joke.